Is primaquine useful and safe as true exo-erythrocytic merontocidal, hypnozoitocidal and gametocidal antimalarial drug? - Francisco Javier López-Antuñano (Instituto Nacional de Salud Pública, 1999)
The main objective of this paper is to make available in a single document, a sequence of events that have been published on the biology of malaria parasites and their interaction with the human host, looking for arguments for effective and save treatment: what we know and what we would like to know about the effects of primaquine in order to justify its use in clinical and public health practice. The practicioner should be aware that the antimalarial activity, hemolytic and methemoglobinemic side effects, and detoxification of primaquine are all thought to depend on various biotransformation products of the drug. In spite of the universal use during over six decades, their site and mechanism of formation and degradation and their specific biologic effects remain very poorly understood in human beings. The mature gametocytes of P. falciparum are naturally resistant to chloroquine and other blood merontocides, but they are usually eliminated with a single dose of 1.315 mg/kg per os (p.o.) of primaquine phosphate (equivalent to 0.75 mg-base). Rather than empirically, related with relapses frequency, dosage schedules should only be determined through consideration of the kinetics and dynamics of the drug and its effect on sporozoites, pre and exo-erythrocytic merontes, hypnozoites and gametocytes of P. vivax. Where medical care services are not available or not capable to detect glucose -6- phosphate dehydrogenese- (G-6-PD) deficiencies and deleterious effects of the drug, we recommend not to use primaquine. Both, P. vivax primary clinical attack and P. vivax relapses, as and when they occur should be treated with a course of 10 mg/kg chloroquine-base p.o. Prevention of relapses is probably related to strain characteristics of P. vivax hypnozoites populations envolved. If well informed and qualified medical care workers decide to use primaquine in the absence of enzime defficiencies and are able to follow-up the clinical, toxicological and parasitic results, a daily dose of 0.25 mg/kg primaquine-base during 14 days could be administered safety for possible prevention of P. vivax relapses. El objetivo principal de este ensayo es poner a disposición en un documento único, una secuencia de eventos que han sido publicados sobre la biología de los parásitos del paludismo y su interacción con el huésped humano, buscando argumentos para el tratamiento eficaz y seguro: ¿qué sabemos y qué nos gustaría saber sobre los efectos de la primaquina para justificar su uso en la práctica clínica y de salud pública ? El profesional debe estar atento a que tanto la actividad antipalúdica, como los efectos deletéreos hemolíticos y metahemoglobinémicos y de detoxificación de la primaquina dependen de varios productos de biotransformación de la droga. No obstante el uso universal durante seis décadas, el sitio y mecanismo de formación y degradación y sus efectos biológicos específicos en los seres humanos aún permanecen poco comprendidos. Los gametocitos maduros de Plasmodium falciparum son naturalmente resistentes a la cloroquina y a otras drogas merontocidas sanguíneas, pero son usualmente eliminados con dosis única de 1.315 mg/kg per os (p.o.) de fosfato de primaquina (equivalente a 0.75 mg base). En relación con la frecuencia de recaídas, en vez de empíricamente, los esquemas de tratamiento deberían determinarse considerando la farmacodinamia de la droga y su efecto sobre los esporozoitos, merontes pre-exo-eritrocíticos, hipnozoitos y gametocitos de P. vivax. Donde no hay servicios de atención médica disponibles, o éstos no están capacitados para identificar deficiencias de glucosa -6- fosfato dehidrogenasa (G6PD) ni efectos deletéreos de la droga, recomendamos que no se use primaquina. Tanto los ataques clínicos primarios como las recaídas de las infecciones por P. vivax como y cuando se presenten deben tratarse con 10 mg/kg de cloroquina base p.o. La prevención de las recaídas por P. vivax está probablemente relacionada con la cepa y las características de las poblaciones de hipnozoitos de P.vivax involucrados. Si los trabajadores de salud bien informados y calificados deciden usar primaquina en ausencia de deficiencias de enzimas y están dispuestos a hacer el seguimiento clínico, toxicológico y parasitológico, pueden administrar con seguridad una dosis diaria de 0.25 mg/kg de primaquina-base durante 14 días para la posible prevención de las recaídas por P. vivax.